Transvaginal ligation of descending branch of uterine artery: could be the first surgical attempt to control post-partum haemorrhage? - Mitidieri, Marco; Picardo, Elisa; Tondo, Pierluigi; Benedetto, Chiara; Danese, Saverio (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Post-partum haemorrhage is the major cause of maternal death worldwide. This severe clinical condition can cause also physical morbidity and psychological distress (anemia, coagulopathy, blood transfusion, anterior pituitary ischemia with delay or failure of lactation, myocardial ischemia, postpartum depression). To date several efforts have been made to prevent and treat this severe condition mainly in three ways: medical, surgical, and interventional radiology even in combination. The surgical approach, needs the knowledge of anatomy of vascular distribution of the uterus. According to Palacios-Jaraquemada the feeding vessels of the body of the uterus is defined S1 area and the lower segment, uterine cervix and upper part of the vagina, S2 area. We report three cases in which the ligation of the descending branch of uterine artery (S2 area) helped the surgeon in the treatment of severe primary post-partum haemorrhage causing a significant reduction in blood loss.